ENTREPRENEURIAL EDUCATION IN AUTOMOBILE TECHNOLOGY AS A PANACEA FOR ADDRESSING UNEMPLOYMENT AMONG GRADUATES IN NIGERIA - Abdulkadir, M.; Alawode, O. D. (Sokoto Educational Review, 2015)
Millennium Development Goals are the most broadly supported, comprehensive and specific development goals the world has ever agreed upon. These goals provide concrete, a numerical benchmark for alleviating extreme poverty in its many dimensions. However, political instability and inconsistencies in the socio-economic policies of the government led to the emergence of a high level of unemployment in Nigeria with its attendant consequences on the attainment of MDGs. This paper, therefore, focuses attention on entrepreneurial education in automobile technology as a panacea for addressing unemployment among graduates. The paper examined the concept of entrepreneurship, entrepreneurship education as well as entrepreneurship skills in automobile technology for the attainment of MDGs. It was recommended that Curriculum should be reviewed to include entrepreneurship as part of technology education which automobile technology is an integral part of, so that the products do not only strive for self-employment and self-reliant but be self-employed, Entrepreneurial skills should be encouraged through the mass media and emphasis should be placed on practical institutional delivery in automobile technology programme with equal emphasis on learner’s activities in every unit of the programme.